2016
DOI: 10.1007/s10867-016-9417-4
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid substitutions [K16A] and [K28A] distinctly affect amyloid β-protein oligomerization

Abstract: Amyloid β-protein (Aβ) assembles into oligomers that play a seminal role in Alzheimer's disease (AD), a leading cause of dementia among the elderly. Despite undisputed importance of Aβ oligomers, their structure and the basis of their toxicity remain elusive. Previous experimental studies revealed that the [K16A] substitution strongly inhibits toxicity of the two predominant Aβ alloforms in the brain, Aβ 40 [K16A] substitution induces formation of more compact oligomers than the [K28A] substitution. If the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 56 publications
2
15
0
Order By: Relevance
“…revealed that changes to oligomer structure are both substitution‐ and alloform‐specific . The [K16A] substitution decreased β‐strand content more and produced more compact oligomer conformations in both Aβ 1–40 and Aβ 1–42 than the [K28A] substitution, implying that compaction of Aβ oligomers associated with reduced N‐terminal flexibility may underlie Aβ oligomer toxicity inhibition . These findings are consistent with in vitro findings by Kaden et al .…”
Section: Do Flexible N‐termini Mediate Aβ Oligomer Activity?supporting
confidence: 88%
See 2 more Smart Citations
“…revealed that changes to oligomer structure are both substitution‐ and alloform‐specific . The [K16A] substitution decreased β‐strand content more and produced more compact oligomer conformations in both Aβ 1–40 and Aβ 1–42 than the [K28A] substitution, implying that compaction of Aβ oligomers associated with reduced N‐terminal flexibility may underlie Aβ oligomer toxicity inhibition . These findings are consistent with in vitro findings by Kaden et al .…”
Section: Do Flexible N‐termini Mediate Aβ Oligomer Activity?supporting
confidence: 88%
“…In line with this experimental study, DMD4B‐HYDRA simulations of [K16A]Aβ 1–40 , [K16A]Aβ 1–42 , [K28A]Aβ 1–40 , and [K28A]Aβ 1–42 oligomerization by Žganec et al . revealed that changes to oligomer structure are both substitution‐ and alloform‐specific . The [K16A] substitution decreased β‐strand content more and produced more compact oligomer conformations in both Aβ 1–40 and Aβ 1–42 than the [K28A] substitution, implying that compaction of Aβ oligomers associated with reduced N‐terminal flexibility may underlie Aβ oligomer toxicity inhibition .…”
Section: Do Flexible N‐termini Mediate Aβ Oligomer Activity?mentioning
confidence: 99%
See 1 more Smart Citation
“…The role of familial mutations of α-synuclein charged residues was attributed to changes in fibril stability arising from alterations in electrostatic interactions [ 144 ]. A high impact of salt bridges was also shown for Aβ peptides, fibrils, and oligomer formation through β-turn stabilization [ 145 , 146 , 147 ]; the destabilization of intra-molecular salt bridges was suggested as a key factor in the copper ions’ binding effect on amyloid β fibrillization [ 148 , 149 ].…”
Section: Unfolded Proteinsmentioning
confidence: 99%
“…To conclude, MD simulations can provide a detailed model of the interaction, aggregation, and sometimes folding of the unfolded proteins, which can then be experimentally verified. It is useful, for example, in comparative investigation of point mutations effect, which is important in the case of amyloidogenic peptides associated with neurodegenerative diseases [ 144 , 147 ]. Notably, modeling of the unfolded protein (or flexible peptide) interactions requires multiple simulations, replica-exchange MD simulations, umbrella sampling, Markov state models, or other techniques to obtain reliable information about the conformational ensemble [ 133 ].…”
Section: Unfolded Proteinsmentioning
confidence: 99%